MOBILE-ASSISTED LANGUAGE LEARNING IN KOREAN LANGUAGE CLASSES: INDONESIAN UNDERGRADUATE STUDENTS’ EXPERIENCES AND PERCEPTIONS - Lubis, Arif Husein; Triarisanti, Risa; Samsudin, Didin; Ansas, Velayeti Nurfitriana (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
The ubiquitous presence of mobile devices has benefited the implementation of foreign language learning through Mobile-Assisted Language Learning (MALL). Previous research highlights the portability aspect of mobile devices such as smartphones that can lead to spontaneous, flexible, and personalized learning activities. However, challenges remain; particularly the connectivity issues. The present study seeks to continue the discussion by investigating 79 Indonesian undergraduate students’ experiences and perceptions of MALL in their Korean language classes. The data were obtained by distributing a questionnaire to the students. The validity and reliability coefficients were also measured. Interview sessions were conducted afterward with eleven students to dig for further explanations. The results demonstrate that most students used smartphones for sending messages to peers, checking notifications, accessing materials, submitting their work, and sending messages to lecturers. Regarding the applications used, they frequently utilized smartphones for accessing Google Classroom, Zoom, and WhatsApp during their Korean classes. The results also revealed that while they perceived MALL as useful and flexible for learning Korean toward increased language skills, motivation, autonomy, and critical thinking, technical problems, and connectivity issues remain to be the main challenges. This study discusses some concerns in implementing MALL and its implications for future research.